The 1.4-Mb CMT1A Duplication/HNPP Deletion Genomic Region Reveals Unique Genome Architectural Features and Provides Insights into the Recent Evolution of New Genes - Inoue, Ken; Dewar, Ken; Katsanis, Nicholas; Reiter, Lawrence T.; Lander, Eric S.; Devon, Keri L.; Wyman, Dudley W.; Lupski, James R.; Birren, Bruce

(untitled) (Genome Research, 2001)
Duplication and deletion of the 1.4-Mb region in 17p12 that is delimited by two 24-kb low copy number repeats (CMT1A–REPs) represent frequent genomic rearrangements resulting in two common inherited peripheral neuropathies, Charcot-Marie-Tooth disease type 1A (CMT1A) and hereditary neuropathy with liability to pressure palsy (HNPP). CMT1A and HNPP exemplify a paradigm for genomic disorders wherein unique genome architectural features result in susceptibility to DNA rearrangements that cause disease. A gene within the 1.4-Mb region,PMP22, is responsible for these disorders through a gene-dosage effect in the heterozygous duplication or deletion. However, the genomic structure of the 1.4-Mb region, including other genes contained within the rearranged genomic segment, remains essentially uncharacterized. To delineate genomic structural features, investigate higher-order genomic architecture, and identify genes in this region, we constructed PAC and BAC contigs and determined the complete nucleotide sequence. This CMT1A/HNPP genomic segment contains 1,421,129 bp of DNA. A low copy number repeat (LCR) was identified, with one copy inside and two copies outside of the 1.4-Mb region. Comparison between physical and genetic maps revealed a striking difference in recombination rates between the sexes with a lower recombination frequency in males (0.67 cM/Mb) versus females (5.5 cM/Mb). Hypothetically, this low recombination frequency in males may enable a chromosomal misalignment at proximal and distal CMT1A–REPs and promote unequal crossing over, which occurs 10 times more frequently in male meiosis. In addition to three previously described genes, five new genes (TEKT3, HS3ST3B1, NPD008/CGI-148, CDRT1, andCDRT15) and 13 predicted genes were identified. Most of these predicted genes are expressed only in embryonic stages. Analyses of the genomic region adjacent to proximal CMT1A–REP indicated an evolutionary mechanism for the formation of proximal CMT1A–REP and the creation of novel genes by DNA rearrangement during primate speciation.